Digitally deconvolving the tumor microenvironment. Issue 1 (December 2016) - Aran, Dvir; Butte, Atul
Abstract Understanding a tumor's complex cellular heterogeneity will be crucial for the development of better treatment strategies. A new study suggests a novel method for the in silico dissociation of solid tumors and presents novel insights that have implications for immunotherapy in cancer. Please see the related Research article:www.dx.doi.org/10.1186/s13059-016-1028-7 .